Hubungan antara peran orang tua dan pola asuh dengan perilaku seks pra nikah pada remaja di SMKN 1 Seyegan - Rizka Ayu Nurhatati (Sahabat Publikasi Kuu, 2023)
Background :Teenager is a period when students are confused about their identity so that at this period teenagers are still looking for who they really are. At this period they tend to be more open with friends and prone to falling into juvenile delinquency, including pre-marriage sex. Parents play an important role in this matter both in the parental role and parenting style given to their children.Objective:The research aims to find out how the relationship between the parental role and parenting style with pre-marriage sex behavior in teenagers.Method: This study uses a correlation analytical design with a cross sectional research design. The samples in this study were 33 respondents consisting of teenagers in class X and XI. The instruments used were parental role questionnaires, parenting styles, and pre-marriage sex behavior. Bivariate data analysis applied Somers'd test and Contingency Coefficient.Results: The results of this study indicate that the majority of respondents get moderate parental roles (66.7%) and the majority of democratic parenting styles (69.7%), as well as pre-marriage sex behavior in the moderate category (57.6%). The results of the analysis of the relationship between the parental role and pre-marriage sexual behavior obtained a p value of 0.025 with an r value of -0.342 and an analysis of the relationship between parenting style and pre-marriage sexual behavior obtained a pvalue of 0.334.Conclusion: There is a relationship between the parental role and premarriage sex behavior in teenagers and there is no relationship between parenting style and pre-marriage sex behavior in teenagers at SMK N 1Seyegan.Keywords: Parental role, parenting style, pre-marriage sex behavior, teenagers